Time-dependent reliability analysis for function generation mechanisms with random joint clearances. (October 2015) - Zhang, Junfu; Du, Xiaoping
Abstract: Time-dependent reliability method for mechanisms predicts the probability of satisfying the motion requirement in a predefined period of time. The current reliability methods do not consider the random clearances in mechanism joints. This work extends the current methods into function generation mechanisms on which the effect of random joint clearances is significant. The motion output is approximated in the first order with respect to random dimension variables and in a higher order with respect to random joint clearances by the Hybrid Dimension Reduction Method. This treatment achieves an optimal balance between accuracy and efficiency. Then an envelope method is used to calculate the time-dependent reliability. The method is demonstrated by the analysis of three four-bar function generation mechanisms. Highlights: Joint clearances are stochastic, and they affect kinematic and dynamic performances of mechanisms. The Hybrid Dimension Reduction Method is applied to build the probabilistic model of random joint clearances. An envelope method is used to evaluate the time-dependent reliability of linkage mechanism.